QUALITY MANAGEMENT CHALLENGES IN CONSTRUCTION PROJECTS: INVESTIGATING FACTORS, MEASURES, AND THE ROLE OF MATERIAL QUALITY CONTROL - Chin, Hon Sin; Ting, Sim Nee; Lee, Yee Yong (Malaysia Insititute of Planner, 2024)
In spite of the considerable advancements and enhancements that quality assurance and control have undergone in the construction industry, quality of the products remain an issue. Notable prevalence of poor quality in final products and facilities such as premature defects, repairs and reworks, and overall product failures within construction projects continue to affect both end users and project stakeholders. This study delved into the intricacies of the role of material as a contributor to poor construction quality, specifically in the context of building projects. Results showed that the utilisation of non-compliant and poor-quality materials during construction primarily stemmed from lack of quality assurance/quality control (QA/QC) activities and lack clarity in QA/QC process as prominent factors for poor quality construction material. In addition, the inability of the project supervisory team to identify, rectify by removing or replacing these poor-quality materials at critical work junctures is also a substantial contributory factor. The results underscore the necessity for an enhanced QA/QC framework that possesses the capacity to comprehensively identify, address, rectify, and if required, replace materials that fall short of the stipulated standards and regulations. By resolving the issues of utilisation of poor materials, it is hopeful that substantial improvements to the overarching quality issues of construction projects can be achieved.